FACTORS RELATED TO POSYANDU CADRES’ ACTIVENESS IN PUSKESMAS KUTABARO WORKING AREAS OF ACEH BESAR DISTRICTS - Rahmayani Rahmayani; Muliana Muliana; Marniati Marniati (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
The research objective is to determine the factors related to Posyandu cadres Activeness in Puskesmas Kutabaro working areas of Aceh Besar Districts in 2014. This study is analytical descriptive using cross-sectional design. The population is all cadres of Posyandu which the total amounts are 261 people. The samples in this study are 72 people by using proportional sampling technique followed by random sampling by drawing. The study was conducted on February, 6th-27th 2014 at Puskesmas Kuta Baro. The research results mention that by using statistic test result that there is no relation to the community support, no relation to the appreciation, no relation to the training, and no relation with the facilities, against the Activeness of the Posyandu cadres. The research are no relations among the community support, training and the facility available to Activeness of the Posyandu cadres the support, but there is a relation between the appreciation and Activeness of the Posyandu cadres. Keywords:Community Support, Facilities, Activeness, Training, Appreciation